ANALYSIS OF RADIATION SAFETY IN THE NPP SITE IN NORMAL OPERATION CONDITION - Pande Made Udiyani; Ihda Husnayani (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2017)
ANALYSIS OF RADIATION SAFETY IN THE NPP SITE IN NORMAL OPERATION CONDITION. Construction of nuclear power plant (NPP) requires an evaluation of radiation safety which proves that operation of the NPP under normal operating condition and postulated abnormal conditions is safe. Analysis of radiation safety at the NPP site under normal operating condition is required to complete the documents of site analysis and safety analysis. This study is aimed to obtain radiation dose in the environment of the NPPs at Sebagin site in province of Bangka Belitung. The doses were calculated using PC-Cream code. It is assumed that there are three 1000-MWe PWR operating in Sebagin site. Input data required for PC-Cream simulation are routine sourceterm of three 1000MWe-PWRs, meteorological data, and agricultural and animal production, and population distribution. The meteorological data consist of stability frequency of weather for 16 sectors (wind direction) taken from local weather data for 1 year. The data of agricultural and livestock production and population distribution are also taken for 1 year for 16 sectors and 20 radial directions. The results show that the maximum dose from all types of radionuclides and all pathways accepted by adult public around Sebagin site is approximately 0.053 mSv/year to the north direction in the radius of 1 km. This dose is far below the dose limit value of 1 mSv/year or dose constraint of 0.3 mSv/year as public acceptance criteria (BAPETEN). It can be concluded that radiation doses are influenced by activity and type of nuclides sourceterm, reactor layout, meteorological condition, and environmental condition.